Upaya Meningkatkan Kemampuan Belajar Berhitung Permulaan Bagi Anak Usia 5-6 Tahun dengan Penggunaan Media Stick Pouch di TK Nusantara Plus School - Tiara Galuh Mahaputri; Roza Yenita; Wening Rahayu (EduInovasi: Journal of Basic Educational Studies, 2024)
Efforts to Improve Initial Counting Skills in Children Aged 5-6 Years Through the Use of Stick Pouch Media at TK Nusantara Plus School Bekasi" (2024). Thesis. Bekasi: Universitas Panca Sakti Bekasi, 2024. This study aims to determine the improvement in initial counting skills in children aged 5-6 years through the use of stick pouch media at TK Nusantara Plus School Bekasi. The research uses classroom action research methods, focusing on classroom situations, known as classroom action research. This method involves interaction, communication, collaboration, and participation between researchers and target groups to continuously improve learning. The study was conducted in two cycles to observe the improvement in initial counting skills through the use of stick pouch media, with each cycle consisting of planning, action implementation, observation, and reflection. The subjects of the study were 10 children aged 5-6 years from group B2, consisting of 5 boys and 5 girls, at TK Nusantara Plus School Bekasi. The results showed that the students' counting skills increased from 49.3% in the pre-cycle to 58.7% in cycle I and 85% in cycle II. This indicates that the stick pouch media can be applied to improve the initial counting skills of children aged 5-6 years at TK Nusantara Plus School Bekasi. The results of this study suggest that the method of enhancing initial counting skills using stick pouch media can be successful and meet the completion threshold of 75%.